2004
DOI: 10.1249/01.mss.0000135776.09613.0d
|View full text |Cite
|
Sign up to set email alerts
|

DAQIHF: Methodology and Validation of a Daily Activity Questionnaire in Heart Failure

Abstract: The questionnaire seems reliable, sensitive and valid for the estimation of DEE. VO2(peak) appears related to global DEE and more particularly to activities above 3 METs in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…61 A number of the instruments reviewed here have been modified to suit cardiac patients. 21,24,32,45 With most of these instruments, corresponding validation studies have not been reported. Furthermore, it is useful to present testretest correlations for overall activity, as well as activity according to intensity and type.…”
Section: Concerns With Estimates Of Validitymentioning
confidence: 99%
“…61 A number of the instruments reviewed here have been modified to suit cardiac patients. 21,24,32,45 With most of these instruments, corresponding validation studies have not been reported. Furthermore, it is useful to present testretest correlations for overall activity, as well as activity according to intensity and type.…”
Section: Concerns With Estimates Of Validitymentioning
confidence: 99%
“…It is out of the scope of the present study to discuss the respective interests to use estimates of daily energy expenditure or of maximal aerobic fitness in determinants of metabolic homeostasis. We also tried to point out PAEE in the present study by a validated (against V O2peak ) questionnaire procedure [42]. Questionnaires were administered for autofilling by each subject which probably leads to uncertain data capture (data not shown); this is in line with debates upon the use of self-reported questionnaires to assess physical activity [42].…”
Section: Discussionmentioning
confidence: 92%
“…We also tried to point out PAEE in the present study by a validated (against V O2peak ) questionnaire procedure [42]. Questionnaires were administered for autofilling by each subject which probably leads to uncertain data capture (data not shown); this is in line with debates upon the use of self-reported questionnaires to assess physical activity [42]. Independently, the level of physical activity was also grossly interpreted during the interview preceding the medical examination.…”
Section: Discussionmentioning
confidence: 93%
“…The Population Physical Activity Questionnaire (POPAQ) was used to assess daily physical activity through a set of 82 items investigating all components of physical activity over the previous week and allowed to calculate the quantity of moderate‐to‐vigorous physical activity.…”
Section: Methodsmentioning
confidence: 99%